Compare Open Testicular Biopsy and Testicular Fine Needle Aspiration (TEFNA) for Spermatogenesis in terms of Johnsen’s Scoring in patients with Suspicion of Obstructive Azoospermia - Amanullah Bhutto, Tufail Hussain Tahir, Rukhsana Saboor, A Saboor Soomro, Muhammad Rizwan, Muhammad Younus Jamal Siddiqi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Testicular biopsy is an invasive diagnostic tool to evaluate spermatogenesis and has to be performed only following strict criteria. Objective: To compare open testicular biopsy and testicular fine needle aspiration (TEFNA) for spermatogenesis in terms of Johnsen’s scoring in patients with suspicion of obstructive azoospermia. Materials and Methods: This comparative study was conducted in Pathology department, Ghulam Mohammad Mahar Medical college, Sukkurduring 2021 to 2022. Detailed history was taken and physical examination was carried out including examination of external genitalia. Amongst them, men with normal testicular size and bilaterally palpable vas deference were investigated further regarding their hormone profile (FSH, LH, and Testosterone) and scrotal color doppler ultrasound (CDUS). Procedure was performed under local anesthesia (Spermatic cord block). Results: The mean age of patients in our study was 38.9±6.4 year with minimum age as 28 and maximum as 50 year. In this study, ages were categorized in two groups; one is 20-35 years age group and second is 36-50 years age group. There were 14(35.0%) patients in 20-35 years age group, while 26(65.0%) in 36-50 years age group. Practical implication: This article will helps to improve the technique for confirmation of presence of mature sperms. Conclusion: TEFNA is more reliable and minimal invasive technique for confirmation of presence mature sperms in men with obstructive azoospermia and is associated with minimal complications. Keywords: TEFNA, Sperms, Azoospermia, Complications